Increment of the collective pinning energy in Na1 − xCa x Fe2As2 single crystals with random point defects introduced by proton irradiation - Haberkorn, Nestor Fabian; Kim, Jeehoon; Maiorov, B.; Usov, I.; Chen, G. F.; Yu, W.; Civale, L. (IOP Publishing, 2014)
Fil: Haberkorn, Nestor Fabian. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina